SIKOR North Saami corpus - Giellatekno; Divvun (DataverseNO, 2016)
SIKOR North Saami corpus is a monolingual text corpus of North Saami that contains administrative, law, religious, non-fiction, fiction, and science texts. It is work done at Giellatekno at UiT, Divvun at the Norwegian Saami Parliament, and members of the language communities. Please contanct the institution!